2021
DOI: 10.1186/s13014-021-01766-w
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric study between a single isocenter dynamic conformal arc therapy technique and Gamma Knife radiosurgery for multiple brain metastases treatment: impact of target volume geometrical characteristics

Abstract: Purpose To compare linac-based mono-isocentric radiosurgery with Brainlab Elements Multiple Brain Mets (MBM) SRS and the Gamma Knife using a specific statistical method and to analyze the dosimetric impact of the target volume geometric characteristics. A dose fall-off analysis allowed to evaluate the Gradient Index relevancy for the dose spillage characterization. Material and methods Treatments were planned on twenty patients with three to nine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The Gη 12Gy indices reported for CyberKnife and Gamma Knife plans in this study (figure 3 and table 6) were similar to the range of 44.0% to 51.2% observed by the authors who initially proposed the quality index (Dimitriadis and Paddick 2018). Chea et al (2021) did note the superiority of the dedicated SRS platforms could be due to quality index being more favourable to these systems as a consequence of the relatively higher mean dose of each target and lower V12Gy volumes exhibited by these platforms. Unfortunately, a lack of studies involving linac based SRS plans for multiple brain metastases utilising this plan quality index made it difficult to ascertain if the values recorded for the HyperArc plans are to be expected.…”
Section: Discussionsupporting
confidence: 87%
“…The Gη 12Gy indices reported for CyberKnife and Gamma Knife plans in this study (figure 3 and table 6) were similar to the range of 44.0% to 51.2% observed by the authors who initially proposed the quality index (Dimitriadis and Paddick 2018). Chea et al (2021) did note the superiority of the dedicated SRS platforms could be due to quality index being more favourable to these systems as a consequence of the relatively higher mean dose of each target and lower V12Gy volumes exhibited by these platforms. Unfortunately, a lack of studies involving linac based SRS plans for multiple brain metastases utilising this plan quality index made it difficult to ascertain if the values recorded for the HyperArc plans are to be expected.…”
Section: Discussionsupporting
confidence: 87%
“…Such an experience was based on the use of Gamma Knife radiosurgery whose excellent conformity index, Paddick index, dose fall-off and gradient index, especially in challenging situations (i.e. irradiation of adjacent or critically located targets [48] , [49] , [50] ), characterize a different dose distribution in healthy brain tissue with respect to the LINAC-based stereotactic technique, thus being able to produce different neurocognitive outcomes [51] . An evaluation of these is therefore useful and should be carried our for both techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a LINAC-based RT technique-namely Volumetric Modulated Arc Therapy (VMAT), which was typically employed for limiting radiationrelated adverse events in extracranial sites [14,15]-has been enhanced with advanced Treatment Planning Systems (TPS) to plan a simultaneous radiation dose delivery to multiple brain metastases with maximal sparing of healthy tissue, similarly to what is achievable with GK [8]. Regarding the therapeutic index, these two stereotactic techniques constantly confront dosimetric challenges, and no clinical study has yet confirmed a clear benefit of the one over the other [16]. CK and GK are irreplaceably useful for RT treatments of extremely challenging targets wrapped around critical structures [17].…”
mentioning
confidence: 99%